Implementing Sustainability Development (SDGs) Within Fisipol Unesa to Realize an Environmentally Friendly and Inclusive Campus - Desita Putri Pratama; Nur Farikhatun Nisa; Kharisma Reza Oktavia; Maudelyne Nasywa Maulida; Hervina Mahasrian Putri Asmarani (International Journal of Geography, Social, and Multicultural Education, 2025)
AbstractSDGs (Sutainable Development Goals) are a series of 17 global goals which have been planned by the United Nations in 2015, SDGs prioritize three main aspects, namely economic, social and environmental, the purpose of the existence of SDGs is to create a better and sustainable world, The campus is an important place for the implementation of SDGs because the campus area is a place of learning and a center of innovation for social change that can encourage sustainability, several well-known campuses have had SDGs programs, one of which is the Surabaya State University (UNESA) campus, especially the Faculty of Social and Political Sciences (FISIPOL), FISIPOL is one of the faculties at Surabaya State which has become an SDGs campus. The campus provides facilities and activities that move students within the scope of FISIPOL to actively participate in making the campus environmentally friendly, this article contains the results of a survey on how the role of students and awareness of FISIPOL students about the importance of the role of students in realizing an environmentally friendly campus. The campus also has an important role as a driving force for students to have facilities and support to implement SDGs in the campus area, how the campus can properly facilitate students and strive for their role as a driver of the SDGs program. Keywords: SDGs, Students, Campus, Eco-friendly Campus, FISIPOL